Advertising and New Information Communication Technologies (ICT) - Pereira, Francisco José Costa (2008)
New Information and Communication Technologies (ICTs) are increasingly popular in marketing communications as more and more firms shift from mass marketing to one-to-one marketing. There are many exciting examples of these new technological applications. They include mobile marketing techniques such as SMS (short message service) and MMS (multimedia message service), as well as chatting, multiplayer games, bulletin boards, and raking sites. Interactive Digital TV (IDTV) offers another example of new ICT application in marketing communicatios: the telescopic advertisement, a 30-second TV ad with a call-to-action button which makes it possible to obtain additional information. Our understanding of these new ICT formats is still in its infancy, but empirical research is growing. We have selected five fine studies from this new field.